Internal Transcribed Spacer (ITS) gene as an accurate DNA barcode for identification of macroscopic fungus in Aceh (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Harnelly E, Kusuma HI, Thomy Z, Samingan. 2022. Internal Transcribed Spacer (ITS) gene as an accurate DNA barcode for identification of macroscopic fungus in Aceh. Biodiversitas 23: 2369-2378. Fungal identification is crucial in determining the fungal’s role and benefits and is usually carried out by morphological observation. However, this technique takes a long time and depends on the accuracy of an expert. Therefore, the present study aimed to examine the accuracy of the Internal Transcribed Spacer (ITS) gene to identify macroscopic fungi from Aceh, Indonesia. 23 samples were collected from the Pocut Meurah Intan Grand Forest Park in Aceh, Indonesia. Samples were extracted, amplified, electrophoresed, and sequenced. The nucleotide sequence of the amplified products was analyzed by using the Basic Local Alignment Search Tool (BLAST). 7 out of the 11 samples with good and regular peaks were continued until further analyzed using BLAST. The results showed that samples aga2, aga4, aga5, aga6, aga9, rus, and pol were identified as Pleurocollybia sp., Pleurotus djamour, Filoboletus manipularis, Schyzophillum commune, Gymnopilus lepidotus,Auriscalpium vulgare, and Gyrodontium sacchari, respectively. The study findings indicate that the use of the ITS gene as a barcode effectively separates up to the species level from the type. This is very helpful in the identification process, especially when distinguishing cryptic species clearly because of their similarity, which is difficult to distinguish morphologically.